2017
DOI: 10.1016/j.maturitas.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the incidence of and risk factors for hip fracture: A 16-year longitudinal study in a southern European population

Abstract: The IR of hip fractures was three times higher among women. Illiteracy and clinically significant depression among women and active smoking and disability (HR=3.14) among men independently increased the risk, but dementia did not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
2
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 30 publications
6
37
2
3
Order By: Relevance
“…We did find a positive gradient in the association between smoking and fracture risk, with a 17% to 44% increased hazard of fracture among those men who reported smoking at least 6 and 21+ cigarettes per day, respectively, which is in accordance to what has been previously published . Our baseline data were collected among young adults, mostly aged 18, and therefore while bone is still building up.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We did find a positive gradient in the association between smoking and fracture risk, with a 17% to 44% increased hazard of fracture among those men who reported smoking at least 6 and 21+ cigarettes per day, respectively, which is in accordance to what has been previously published . Our baseline data were collected among young adults, mostly aged 18, and therefore while bone is still building up.…”
Section: Discussionsupporting
confidence: 89%
“…(20) Afterwards, evidence has been piling up linking smoking with fractures in men. (18,19,21) The association with alcohol is less consistent; although hip fracture risk appears to decrease among those consuming up to one drink per day compared with abstainers and with heavy drinkers, the same is not reported for other fracture sites. Moreover, the association between alcohol and bone mineral density differs by sex.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…16, 108 109 Men´s health seem to be more likely to be affected by "risky" behaviour such as smoking or drinking alcohol, 83,110,111 whereas women´s health is influenced by more structural and psychosocial factors. 112,113 However, sex discrimination in health-care expenditure with a consequent survival advantage for men is well-known in some countries, 67, 114 so much so that female patients assess the quality of their hospital care significantly worse than do male patients, and call for better nursing care and better management of their pain. 115 A recent Swedish study has shown that male patients with trauma were more likely than women to obtain the highest prehospital priority, and to be transported directly to a designated trauma centre, 116 despite the fact that Sweden is at the forefront of promoting equity between the sexes.…”
Section: Medical Interventionsmentioning
confidence: 99%